1997
DOI: 10.1159/000201464
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Xanthine-Xanthine Oxidase System and Neutrophils in the Development of Acute Gastric Mucosal Lesions in Rats with Water Immersion Restraint Stress

Abstract: In rats subjected to water immersion restraint (WIR) stress for 1, 3, and 6 h, gastric mucosal lesions developed time-dependently with an increase in lipid peroxide (LPO) levels and a decrease in nonprotein sulfhydryl levels in the gastric mucosa. The gastric mucosal xanthine oxidase (XO) activity significantly increased with the conversion of xanthine dehydrogenase (XD) to XO at 6 h of WIR (3.2-fold that of the control group without WIR). A significant increase in myeloperoxidase (MPO) activity, an index of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
66
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 29 publications
13
66
0
Order By: Relevance
“…It can be readily converted to L-arginine, in the kidney, vascular endothelium and other tissues, thus raising its plasma and tissue levels. (Solomonson et al,2003).From this study, it was found that L-arginine increases the mucus secretion to 11.30±2.64**mg/tissue from 7.4±1.58*in the control as shown in Table 1, which supports the report by Liu et al,2008 andNishida et al,1997). As an indirect precursor of L-arginine, Lcitrulline has a cardioprotective effect, Previous studies have observed reduction in brachial BP after oral L-arginine supplementation in adults with high BP and concurrent chronic diseases (Palloshi et al, 2004).…”
Section: Discussionsupporting
confidence: 87%
“…It can be readily converted to L-arginine, in the kidney, vascular endothelium and other tissues, thus raising its plasma and tissue levels. (Solomonson et al,2003).From this study, it was found that L-arginine increases the mucus secretion to 11.30±2.64**mg/tissue from 7.4±1.58*in the control as shown in Table 1, which supports the report by Liu et al,2008 andNishida et al,1997). As an indirect precursor of L-arginine, Lcitrulline has a cardioprotective effect, Previous studies have observed reduction in brachial BP after oral L-arginine supplementation in adults with high BP and concurrent chronic diseases (Palloshi et al, 2004).…”
Section: Discussionsupporting
confidence: 87%
“…Cold immobilization stress is a commonly used and clinically relevant experimental model for stress-induced gastric mucosal lesions (5)(6)(7). This model requires at least 6 h to form profound hemorrhagic necrotic lesions in the gastric mucosa (12,15). The finding of the current study showed that when rats were exposed to cold immobilization stress for a total of 6 h, phosphorylation/activation as well as activity of p38 kinase in gastric mucosa was remarkably up-regulated at as early as 15 min after the start of stress and still persisted until the end of stress.…”
Section: Discussionmentioning
confidence: 99%
“…Under this hypoxic-ischemic condition, reactive oxygen species (ROS) 4 such as superoxide anions, hydrogen peroxide, and hydroxyl radicals are rapidly and continuously produced, and the resulting oxidative stress is proven crucially responsible for the development and progression of epithelial necrosis and mucosal ulceration (10 -12). In addition, this hypoxic-ischemic condition is also accompanied by an acute inflammatory response of the gastric mucosa characterized by accumulation of inflammatory cells and a multitude of inflammatory mediators (13)(14)(15)(16). Recruitment and activation of neutrophils contribute greatly to the pathophysiological processes occurring in gastric mucosa at the later stage of stress (13,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Reactive oxygen species (ROS) and nitric oxide ( • NO) generation, lipid peroxidation, and neutrophil infiltration in the gastric mucosal tissue play a critical role in the pathogenesis of WIRS-induced gastric mucosal lesions (2)(3)(4)(5).…”
mentioning
confidence: 99%